(untitled) (Third Sector Social Economic Review, 2023)
Sustainable consumption is one of the seventeen sustainable development goals adopted in 2015. Taking into account the capacity of the world, the main source of financing in reaching the sustainable consumption target, which aims for a good and healthy life for every individual, is taxes, as in the other sixteen targets. While the increase in tax revenues contributes positively to achieving the development goals, the increase in tax compliance serves the sustainable consumption targets by increasing tax revenues. In this context, tax compliance is important in terms of financing sustainable development goals. This importance makes it a priority to examine the factors affecting tax compliance. Social norms are among the factors that affect tax compliance, among other factors. Sustainable consumption is also a development goal influenced by social norms. In this study, it is aimed to examine the relationship between sustainable consumption as a sustainable development goal and tax compliance as a tool serving this purpose. As a result of the field research, it was concluded that there is a relationship between sustainable consumption behavior and tax compliance. In this sense, it can be said that every positive effect of social norms on sustainable consumption behavior can contribute positively to sustainable development by increasing tax compliance and therefore tax revenues.